Zur Zentralörtlichen Struktur Bayerns - Wehling, Hans-Werner (ERDKUNDE, 1975)
Schmook's isodyne method is one of a number of quantitative ways of classifying central place structures which have developed since Christaller. This paper, in which the method is modified to fit the regional statistical data base, has two aims. The first, with the help of the isodyne method, is to work out the bases of the central place structures of Bavaria and to set out their dependence on transport structure and socio-economic processes and conditions. The other is to compare the central place hierarchies and service areas obtained by this method with results from other techniques, in order to test the validity of the isodyne method. In Bavaria the Regierungsbezirke and the planning regions both show a great deal of differentiation in their central place structures. The quantitative isodyne method - given a change in the original computational formula to suit the statistical regional data base - proves an effective and efficient way of revealing these regional differences.